The evolution of sunflower crops in Romania in the context of the pre- and post-accession to the European Union - Andreea-Raluca Chiriac; Stelica Cristea; Mihai Popescu; Luxiţa Rîşnoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The agricultural sector holds a major place in the Romanian economy, with an important contribution to Gross Domestic Product (GDP), Romania being an important pawn over oilseeds market because it produces a significant quantity of sunflower for export. The main purpose of the paper is to study the dynamics of sunflower cultivated area, the registered productions, the average yield per hectare, prices, import and export, all of these in the context of the pre- and post-accession to the European Union.The statistical data have been processed based on fixed indices and average annual growth rate. Oilseeds cultivated area has continuously increased in the analyzed period from 654,7 thousand ha in 1990 to 1.629,5 thousand ha in 2016. In the same year, sunflower cultivated area reached 1.039,8 thousand ha, being by 263,44% higher than in 1990 and 124,4% than 2007, after the postaccession to the European Union. Evolution of the cultivated area (thousand ha), yield (kg/ha) and total sunflower production (thousand tons) has been determined based on the achievements in 2007 and annual growth rate calculated for the period 2008-2016 whose values have been the following ones: for cultivated area: 2,82%; for yield: 16,42%; for production: 15,77%. Sunflower prices reflected a large variation from a year to another, but mainly a continuous increase starting from the year 2007. The increased price is justified by demand/offer ratio and by the increased demand of oilseeds in the internal and external markets.
Keywords: Q17; 330; production; cultivated area; fixed basis index; average annual growth rate; price